Effect of E-Health Use on Cancer Screening Mediated Through Cancer Worry and Fatalism: A Cross-Sectional Study of Older Adults - Yu Zheng PhD; Jiazheng Zayn Wang PhD; Yingxia Zhu PhD; Xinshu Zhao PhD (Cancer Control, 2025)
Introduction Cancer has been one of the major causes of death among older adults. Cancer screening is key for early detection, which may help prevent or alleviate cancer. E-health platforms have been a main discriminator of cancer-related knowledge. The Health Belief Model indicates an association between individual behaviors, intentions, and other psychological factors. Understanding the psychological mechanisms that mediate the effect of E-health use (EHU) on cancer screening intention is crucial for cancer prevention and treatment among older adults. Methods Cross-sectional data were from the National Trends in Health Information Survey 6 (HINTS6). Respondents aged 65-74 years were selected for the study, and the final sample size, excluding missing values, was 925. This study used a parallel mediation model to analyze the mediating role of psychological mechanisms through cancer worry and cancer fatalism. Regression analysis was conducted using SPSS to test the parallel mediation model. Results The study found a direct ( b = .25, b p = .25, P < .001) positive association between E-health use and cancer screening intentions. In addition, this study revealed a parallel indirect association between E-health use and cancer screening intentions mediated by cancer fatalism ( b = .003, b p = .003, 95% CI [.001, .004]) and cancer worry ( b = .05, b p = .05, SE = .002, 95% CI [.04, .05]). Conclusion This study highlights the importance of EHU in promoting cancer screening intentions among older adults in the United States. Access to electronic health information can reduce cancer fatalism and increase cancer worry, ultimately leading to greater interest and intention to undergo cancer screening. These findings have implications for healthcare providers and policymakers aiming to improve cancer screening rates among older adults.